Pago por servicios ambientales: una nueva forma de conservar la biodiversidad - Wunder, Sven; Wertz-Kanounnikoff, Shiela; Morino-Sanchez, R. (2007)
This paper presents a description and analysis of payment for environmental services (PES) schemes worldwide that aims to allow us to understand their logic, scope, and implementation requirements, in particular in relation to preconditions prevailing in developing countries.